2023
DOI: 10.3389/frwa.2023.1227167
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic complexity influences coarse particulate organic matter transport and storage in headwater streams

Caleb B. Fogel,
Katherine B. Lininger

Abstract: Coarse particulate organic matter (CPOM; organic matter 1–100 mm in diameter, excluding small wood) stored in streams provides an important energy source for aquatic ecosystems, and CPOM transport provides downstream energy subsidies and is a pathway for watershed carbon export. However, we lack understanding of the magnitude of and processes influencing CPOM storage and transport in headwater streams. We assessed how geomorphic complexity and hydrologic regime influence CPOM transport and storage in the Color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Their results showed that over 3 years, the CPOM exports in Vuelta de Zorra were ≤36% of the exported large wood. Still, the contribution of CPOM to the organic carbon cycle might be relevant and deserves to be calculated (Fogel & Lininger, 2023).…”
Section: Wood Storage and Kinetics Within Reachesmentioning
confidence: 99%
“…Their results showed that over 3 years, the CPOM exports in Vuelta de Zorra were ≤36% of the exported large wood. Still, the contribution of CPOM to the organic carbon cycle might be relevant and deserves to be calculated (Fogel & Lininger, 2023).…”
Section: Wood Storage and Kinetics Within Reachesmentioning
confidence: 99%
“…The downstream increase of POMBed conglomerates that dissociated into POMBed <1 mm, could cause an underestimation of the POMBed >1 mm flux at El Colorado. The discrepancy may further be due to sampling bias (Turowski et al, 2013), bedload flux variability due to bedforms, the formation of OM waves at the channel bed, interspersed with relatively barren intervals (Heijnen et al, 2022), strongly sustained by discharge (e.g., Rickenmann, 2018;Turowski et al, 2016;Reid et al, 1998), and channel geometry (Fogel and Lininger, 2023). Bedload sampling, particularly using Helley-Smith samplers, can be prone to high variability, and we suggest our estimates are an order approximation (Bunte et al, 2008) that likely underestimate the maximum POMBed transport rate.…”
Section: Mechanical Comminution Of Pombed During Long-range Transportmentioning
confidence: 99%
“…However, organic debris at the river bed is difficult to observe and quantify due to logistical difficulties in sampling and highly variable transport rates (Turowski et al, 2013). The occurrence, recruitment, sources and fate of POMBed during transport has only been addressed for a few headwater streams (Turowski et al, 2016;Turowski et al, 2013;Bunte et al, 2016;Iroumé et al, 2020;Fogel and Lininger, 2023), and even less for lowland systems (Hage et al, 2022;Schwab et al, 2022). The paucity of work on where POMBed is recruited from, and how long it endures long-range fluvial transport after erosion, makes it difficult to build a mechanistic model to predict bedload OC fluxes and quantify their role in the terrestrial OC cycle.…”
Section: Introductionmentioning
confidence: 99%